SELF-CONTROL SEBAGAI PREDIKTOR AGRESI VERBAL PADA MAHASISWA PENGGUNA AKTIF MEDIA SOSIAL - Dinda Fatikawardhani; Tumanggor, Raja Oloan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The intensity of social media use among students can increase the risk of verbal aggression, especially when self-control is low. This study aims to examine the relationship between self-control and verbal aggression among active social media users aged 18-25 years. The participants consisted of 511 students selected through convenience sampling. The study used a correlational quantitative method with the Self-Control Scale  and Verbal Aggressiveness Scale  instruments. Analysis using Spearman's correlation showed a significant negative relationship between self-control and verbal aggression (r = -0.428, p <0.05). These results indicate that the higher the self-control, the lower the tendency to engage in verbal aggression. These findings provide an understanding of the role of self-control in aggressive behavior on social media and can be the basis for developing interventions for students.